Fuzzy Inference System Untuk Menentukan Tingkat Kompetensi Guru Di Bidang Kualifikasi Akademik Dan Pengalaman Mengajar Berbasis Web - Jefri Setiawan; Hindayati Mustafidah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2015)
Competences that to be had by teachers are pedagogic competency, personality competency, social competency and professional competency that to be got through profession education. To know the point of teacher competency it is needed hard accounting so that was created web of system tsukamoto method fuzzy inference system that can be accessed by who ever and where ever. The point of teachers competency can be accessed based on the level of qualification input and teacher experience in teaching so the result is the level of teachers competency that to be seen through academic qualification and teaching experience. How ever, to determine the point of teacher competency neither academic qualification or teaching experience, the both components are only the examples to support to determine the point of teacher competency. Keywords: Fuzzy Inference System, Tsukamoto Methode, Academic Qualification, Teaching Experience, Web.